2019
DOI: 10.3390/ijerph16224559
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Strategy and Corporate Social Responsibility: The Mediating Effect of Triple Bottom Line

Abstract: Limited research in the area of the triple bottom line (TBL) mediation effect on the relationship between organizational strategic performance (OSP) and corporate social responsibility performance (CSRP) has motivated this study. The objective of this study is to investigate how OSP affects CSRP and the mediation impact of TBL elements through the decision-making process of business management. Considering a sample of 250 employees from Bangladesh, this study used structural equation modelling (SEM) to test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 71 publications
1
39
0
1
Order By: Relevance
“…Other studies (Masud et al 2019) have found that economic responsibility has no intervening role while environmental and social responsibility significantly mediated the relationship between organizational strategic performance and corporate social responsibility performance.…”
Section: Literature Review and Current State Of Knowledgementioning
confidence: 84%
See 1 more Smart Citation
“…Other studies (Masud et al 2019) have found that economic responsibility has no intervening role while environmental and social responsibility significantly mediated the relationship between organizational strategic performance and corporate social responsibility performance.…”
Section: Literature Review and Current State Of Knowledgementioning
confidence: 84%
“…Although the authors know that one of important factors of Industry 4.0 is sustainability (Masud et al 2019;Birkel et al 2019), especially in the context of all dimensions of the triple bottom line (TBL)-ecological, social, and economic, environmental factors were not investigated because the required data series were not available. Environmental dimension of the TBL was describe of another authors (Braccini and Margherita 2019), these authors deal with the sustainable use of resources.…”
Section: Basic Datamentioning
confidence: 99%
“…Legitimacy conferral also differs in firms’ relationships with the government and NGOs. A relationship with the government confers political legitimacy, referring to the state perceptions of the firm’s appropriateness and desirability [ 43 ]. Political legitimacy can serve to enable firms to access state resources [ 44 ] and provide a buffer against external institutional uncertainty [ 45 ].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…For defining CS, we build on the study of Lueg and Radlach (2016) which refers to CS as a concept of stakeholder management equally comprising economic, environmental, and social aspects. The literature argues that enterprises that use the triple bottom line (TBL) concept of CS voluntarily deal with social, economic, and environmental issues (people, profit, and planet), remain sustainable and survive in the long run (Van Marrewijk and Werre 2003;Masud et al 2019). In this systematic literature review, we use CS as an umbrella term, while referring to "any concept that addresses the three dimensions of ecological integrity, social responsibility and economic prosperity" (Lueg and Radlach 2016, p. 2).…”
Section: Introductionmentioning
confidence: 99%